Beyond Academic Achievement: A Holistic Evaluation Model for Measuring Cognitive, Spiritual, and Character Development in Islamic Religious Education - Siti Lufniyah; Dina Hermina (Yayasan Pendidikan Tanggui Baimbaian, 2026)
Learning evaluation in Islamic Religious Education (IRE) has traditionally emphasized students’ cognitive achievement, while spiritual and character development core objectives of Islamic education have received limited and fragmented assessment. This study aims to develop a holistic evaluation model capable of measuring students’ cognitive, spiritual, and character development in an integrated manner within Islamic Religious Education. The study employs a qualitative approach using a library research method by examining scholarly literature, educational policies, and evaluation theories from both contemporary educational perspectives and Islamic educational thought. The findings indicate that a holistic evaluation model should integrate three primary dimensions: mastery of Islamic knowledge (cognitive development), internalization of religious values (spiritual development), and the cultivation of Islamic character (character development). Assessment of these dimensions can be conducted through a combination of academic tests, behavioral observations, reflective journals, self-assessment, peer assessment, and learning portfolios. The proposed model provides a more comprehensive approach than conventional assessment practices by evaluating not only academic outcomes but also students’ attitudes, behaviors, and spiritual awareness. The study contributes a conceptual framework for designing more meaningful and goal oriented evaluation systems in Islamic Religious Education, aligning assessment practices with the broader mission of Islamic education in the contemporary era.